Programmatic evaluation of feasibility and efficiency of at birth and 6-week, point of care HIV testing in Kenyan infant - Wexler, Catherine (PLoS One, 2020)
BACKGROUND: Testing infants at birth and with more efficient point of care (POC) HIV diagnostic can streamline EID and expedite infant ART initiation. We evaluated the implementation of at birth and 6-week POC testing to assess the effectiveness and feasibility when implemented by existing hospital staff in Kenya. METHODS: Four government hospitals were randomly assigned to receive a GeneXpert HIV-1 Qual (n = 2) or Alere m-PIMA (n = 2) machine for POC testing. All HIV-exposed infants enrolled were eligible to receive POC testing at birth and 6-weeks of age. The primary outcome was repeat POC testing, defined as testing both at birth and 6-weeks of age. Secondary outcomes included predictors of repeat POC testing, POC efficiency (turnaround times of key services), and operations (failed POC results, missed opportunities). RESULTS: Of 626 enrolled infants, 309 (49.4%) received repeat POC testing, 115 (18.4%) were lost to follow up after an at-birth test, 120 (19.2%) received POC testing at 6-weeks only, 80 (12.8%) received no POC testing, and 2 (0.3%) received delayed POC testing (>12 weeks of age). Three (0.4%) were identified as HIV-positive. Of the total 853 POC tests run at birth (n = 424) or 6-weeks (n = 429), 806 (94.5%) had a valid result documented and 792 (98.3%) results had documented maternal notification. Mean time from sample collection to notification was 1.08 days, with 751 (94.8%) notifications on the same day as sample collection. Machine error rates at birth and 6-weeks were 8.5% and 2.5%, respectively. A total of 198 infants presented for care (48 at birth; 150 at 6-weeks) without receiving a POC test, representing missed opportunities for testing. DISCUSSION: At birth POC testing can streamline infant HIV diagnosis, expedite ART initiation and can be implemented by existing hospital staff. However, maternal disengagement and missed opportunities for testing must be addressed to realize the full benefits of at birth POC testing.